Fine Mapping of the MAP2K5 Region Identified rs7175517 as a Causal Variant Related to BMI in China and the United Kingdom Populations - Lu, Ce; Wang, Hai-Jun; Song, Jie-Yun; Wang, Shuo; Li, Xue-Ying; Huang, Tao; Wang, Hui (Frontiers in Genetics, 2022)
Background: Genome-wide association studies (GWASs) have consistently identified MAP2K5 as an obesity susceptibility gene. To deepen our understanding of the potential causal genetic variants of this region, a fine-mapping study of MAP2K5 was conducted. Methods and Results: SNPs rs7175517 (G > A) and rs4776970 (T > A) were identified as the leading SNPs associated with BMI in both Chinese and the United Kingdom populations. Second, colocalization of GWAS and expression quantitative trait loci (eQTL) analyses and bioinformatic analyses indicated that rs7175517 is the functionally leading variant in the MAP2K5 gene region. Dual-luciferase assays indicated that the G allele of rs7175517 reduced the mRNA expression of MAP2K5 in HEK293T cells. The possible mechanism was that the G allele interacted with more RNA repressors from nuclei extracts, which was evidenced by electrophoretic mobility shift assays (EMSAs). Furthermore, the pathway enrichment analyses of the products from DNA pull-down and protein mass spectrometry demonstrated that the G allele of rs7175517 might interact with RNA catabolic or splicing transcription factors, which consequentially increased adiposity deposition. Conclusion: SNP rs7175517 of the MAP2K5 gene was the putative causal variant associated with BMI. More precisely designed in vitro or animal experiments are warranted to further delineate the function of MAP2K5 in adipogenesis.